Effectiveness of psychoeducational intervention in promoting post-stroke self-care: a systematic literature review - Nungulo, Victor Nhime; Gonçalves, Mauer; Henriques, Maria Adriana; Baixinho, Cristina Lavareda (Frontiers in Rehabilitation Sciences, 2025)
BackgroundStroke is one of the main causes of morbidity and mortality in the world, and sequelae include physical disability, difficulties with independence for self-care, and loss of mobility and quality of life.Objectivethis study was to summarize the evidence about the effectiveness of psychoeducational interventions in promoting post-stroke self-care.MethodsA systematic literature review was carried out per the Cochrane recommendations. The following databases were included: MEDLINE (via PubMed), Scopus, CINAHL Complete, Cochrane, JBI, and B-on. The study as performed between December 2023 and February 2024, according to the eligibility criteria, by two independent reviewers. The bibliographic sample was evaluated for risk of bias using RoB 2, only clinical trials were included.ResultsThe seven articles selected, from 2019 to 2024 evaluated education to promote care and self-care; rehabilitation programmes with physical exercise; management of stress, depression and anxiety; and symptom management. Interventions relating to awareness and knowledge about post-stroke, development of healthy behavior and lifestyle reinforcement of self-care capacity.ConclusionsThis literature review found that in some studies the implementation of psychoeducational interventions improves the knowledge, independence and self-care of this population and their families, although not all of them were equally effective. The results of the articles reinforce that psychoeducational interventions may increase functional independence and the ability to carry out activities of daily living and improve health and quality of life.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023483087, PROSPERO CRD42023483087.